Investigating the Effect of Reward and Punishment on the Student’s Learning Achievement and Discipline - Inda Indrawati; Marzuki Marzuki; Syafi’urrohman Syafi’urrohman; Agung Rinaldy Malik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to investigate the effect of reward and punishment on student achievement and discipline. This study used a descriptive qualitative approach with the sampling technique, namely purposive sampling. The data was collected using interviews and documentation and was analyzed qualitatively. The research results showed several rewards and punishment types contribute to the student's learning achievement and discipline. The types of rewards that contribute effectively to students learning achievement are praise, respect and material prizes, and a sign of appreciation. In contrast, types of punishments that affect the students learning discipline are physical punishment and inconvenient punishment. In conclusion, the effect of reward and punishment on student achievement and discipline, among others, increases student enthusiasm for learning, motivates students to maintain achievement, and makes students more disciplined in learning. Keywords: Discipline, Learning Achievement, Punishment, Reward